2011
DOI: 10.1016/j.econmod.2010.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Economic and productivity growth decomposition: An application to post-reform China

Abstract: This paper examines and applies the theoretical foundation of the decomposition of economic and productivity growth to the thirty provinces in China's post-reform economy. The four attributes of economic growth are input growth, adjusted scale effect, technical progress, and efficiency growth. A stochastic frontier model with a translog production and incorporated with human capital is used to estimate the growth attributes in China. The empirical results show that input growth is the major contributor to econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 65 publications
5
23
0
1
Order By: Relevance
“…This suggests that the region could have further increased their output or real GRP level by 27.63 percent given the same level of capital stock and employment. The result is consistent with the studies by [4]- [6]. Results found that Hubei emerged as the most efficient province in China and this is followed by Hebei and ZheJiang in the Eastern region with an average overall efficiency score of 98.30 percent and 87.50 percent respectively.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This suggests that the region could have further increased their output or real GRP level by 27.63 percent given the same level of capital stock and employment. The result is consistent with the studies by [4]- [6]. Results found that Hubei emerged as the most efficient province in China and this is followed by Hebei and ZheJiang in the Eastern region with an average overall efficiency score of 98.30 percent and 87.50 percent respectively.…”
Section: Resultssupporting
confidence: 82%
“…This is consistent with the regional studies in China, e.g. [4], [5] and [6]. This needs to be address by better policy implementation in order to avoid the effects of inequality towards the economic development in China.…”
Section: Conclusion and Recommendationsupporting
confidence: 67%
“…A fully nonparametric time-variant stochastic frontier model has been specified to allow for province effects and time effects to enter the production function with other inputs in a nonparametric way. The The empirical findings in this paper have improved the discussion on China's productivity analysis, echoed on such recent discussions as regional inequality, disparity in growth inputs and human capital development in China's post-reform economic development (Wu, 2008;Li and Liu, 2011;Chang, 2002;Fleisher and Zhao, 2010;Liu and Li, 2006;Chi, 2008;Li et al, 2009 …”
Section: Resultsmentioning
confidence: 97%
“…Nonetheless, studies on China's post-reform economy have provided a continued debate on whether technical progress or technical efficiency is the more important contributing factor to China's TFP growth (Wu, 2000;Li and Liu, 2011). After more than three decades of economic reform since 1978, it would be useful to examine if technical efficiency has become an important factor in China's growth.…”
Section: Introductionmentioning
confidence: 99%
“…The study in Li (2009) extended the TFP estimates by using ownership data, and following the endogenous growth models the human capital variable has been incorporated to examine China's post-reform performance of TFP and its relative variance. The aggregate nature of TFP has further been decomposed into the three components of productivity, technical efficiency and scale economy in post-reform China (Li and Liu, 2011). …”
Section: Introductionmentioning
confidence: 99%